Early seed plants in the Southern Hemisphere: I. Associated ovulate and microsporangiate organs from the carboniferous of Peru - Erwin D.M. (1994)
Palma for their assistancien the field; G. Christian Amstutz for help in early phaseso f the project; Winfried Remy for assistanceg etting literature; Sarah A. Riley for plant illustrations;P hillip M. Willson for drafting the sectiona nd locality maps; and Manoj Aggarwal for photographica ssistance. This research was supportedb y grants from the National ScienceF oundation( EAR-8916826a) nd the Research Foundation of the University of Pennsylvaniat o HWP, and a grant from the Consejo Nacional de Ciencia y Tecnologia (CONCYTEC) to VA.